The use of the internet for students' performance at institutions of higher learning - Baloyi, Nhlayisi Cedrick (My University, 2021)
This study focuses on the use of the internet for students’ academic performance at institutions of higher learning. Various internet applications including search engines, online library resources and social media are evaluated to explore how best they can be used to enhance students’ performance at institutions of higher learning. This is critical to ensure that students maximise the use of technology specifically for academic purposes. Generally, students are constant users of the internet at institutions of higher learning, hence it is cardinal to examine their internet use patterns for academic purposes. Institutions of higher learning have invested in advanced technology through the internet to enhance student academic purposes. Therefore, one would expect students to use various internet applications effectively for the betterment of their studies. In this study, the researcher used both qualitative and quantitative research methodologies. The researcher also employed exploratory and descriptive designs. These methodologies and designs are appropriate for this study because they allow data to be collected through focus group interviews and questionnaires. Focus group interviews were employed to collect qualitative data and questionnaires were used to collect quantitative data. The researcher conducted six focus groups from three institutions of higher learning, namely the University of Limpopo, University of Venda and Tshwane University of Technology, Polokwane campus. Three hundred and forty-three (343) questionnaires were analysed for this study. These data collection tools were pertinent for this study since they assist to determine factors that influence the attitudes, opinions and behavior of the participants. Online library resources play a cardinal role in enhancing the learning process for students by providing online content which could have been difficult to access without the internet. Social media improve and enhance students’ academic performance, but students do not know how best to use it for academic purposes. Proper integration of social media into education is needed. In contrast, students prefer to use social media purely for socialising and entertainment. Despite their ability to assist students in enhancing and improving learning process, social media are, mostly not used for academic purposes. xiv Additionally, students’ use of internet search engines exposes them to an array of information which require critical online information literacy in order to choose the best information. Lastly, the study contributes to the existing body of knowledge by creating a model which will enhance and assist students to easily access academic information through the use of a mobile application. The study also provides significant information which could be used to amend and draft new ICT policies within institutions of higher learning, taking into consideration the adoption of online learning through the use various technologies including social media.
Thesis (Ph. D. (Media Studies)) -- University of Limpopo, 2021
Keywords: Internet use; Students; Institutions of higher learning; Education -- Computer network resources; Education -- Research -- South Africa; Educational technology; Internet users